2022
DOI: 10.3390/pharmaceutics14020284
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclodextrins and Drug Solid State Properties on Flufenamic Acid Dissolution Performance from Tablets

Abstract: Flufenamic acid (FFA) is a non-steroidal anti-inflammatory drug characterised by a low solubility and problems of variable dissolution rate and bio-inequivalence. Different FFA batches, obtained by different suppliers, showed different powder characteristics (particle size, shape and surface properties) that may affect its dissolution behaviour from solid dosage forms. Aim of this work was the improvement of FFA solubility and dissolution rate by the use of cyclodextrins (CDs) and the obtainment of an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the same research, docking studies revealed that umbelliferone was not completely inserted into the α-CD cavity in all poses because of its small cavity size [9]. In the research studies of M. Novac et al [16] and F. Maestrelli et al [17], β-CD and various β-CD's derivatives (2-hydroxypropyl-β-cyclodextrin, (HP-β-CD), randomly methylated-β-CD (RAMEB), and sulfobutylether-β-CD (SBE-β-CD)), in the form of inclusion complexes with APIs such as nimodipine (calcium channel blocker [16]) and flufenamic acid (non-steroidal anti-inflammatory agent [17]), have been incorporated in pharmaceutical tablets via direct compression. The complexation of flufenamic acid with RAMEB remarkably improved its dissolution rate, being a useful tool for the effective Encapsulation is a common technique that is used to protect the encapsulated compounds from adverse environments, and to modify the physicochemical properties of different hydrophobic molecules such as their aqueous solubility and biological profile.…”
Section: Introductionmentioning
confidence: 91%
“…In the same research, docking studies revealed that umbelliferone was not completely inserted into the α-CD cavity in all poses because of its small cavity size [9]. In the research studies of M. Novac et al [16] and F. Maestrelli et al [17], β-CD and various β-CD's derivatives (2-hydroxypropyl-β-cyclodextrin, (HP-β-CD), randomly methylated-β-CD (RAMEB), and sulfobutylether-β-CD (SBE-β-CD)), in the form of inclusion complexes with APIs such as nimodipine (calcium channel blocker [16]) and flufenamic acid (non-steroidal anti-inflammatory agent [17]), have been incorporated in pharmaceutical tablets via direct compression. The complexation of flufenamic acid with RAMEB remarkably improved its dissolution rate, being a useful tool for the effective Encapsulation is a common technique that is used to protect the encapsulated compounds from adverse environments, and to modify the physicochemical properties of different hydrophobic molecules such as their aqueous solubility and biological profile.…”
Section: Introductionmentioning
confidence: 91%